ESTIMASI TINGKAT BAHAYA EROSI (TBE) PADA EMPAT TIPE PENGELOLAAN LAHAN DI DESA KARANG SIDEMEN, LOMBOK (Erosion Hazard Level Estimation of Four Land Use Management Types in Karang Sidemen Village, Lombok) - Sitti Latifah; Eni Hidayati; Diah Permata Sari; Kornelia Webliana (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2023)
Soil erosion is a significant threat to land sustainability and productivity in mountainous areas. Erosion can affect food security and land vulnerability to climate change. This study was conducted to assess the potential erosion and Erosion Hazard Level (TBE) in four types of land management involving the community in Karang Sidemen Village using the Revised Universal Soil Loss Equation (RUSLE) method. The results showed that for each slope class, the Botanical Forest Park (Tahura) Nuraksa Utilization Zone had the lowest potential erosion value, followed by Community Forest (HKm) and Hortipark Tastura. Forest Areas with Special Purpose (KHDTK) Rarung has the highest potential erosion value in all slope classes. For all slope classes, TBE in the Tahura Nuraksa is considered  low-level. Erosion Hazard Levels in Hortipark Tastura, KHDTK Rarung, and HKm are dominated by the moderate category. There were significant high and very high TBE in KHDTK Rarung. Soil erodibility values for all types are low. Potential erosion and TBE in the four management types are strongly influenced by slope and vegetation factors.